Ecological Management Zoning Identification by Coupling Blue-Green and Gray Infrastructure Networks: A Case Study of Guizhou Province, China - Shuang Song; Xuanhe Zhang; Shaohan Wang; Yue Gong (Land)
Ecological management zoning is crucial for maintaining regional ecological security and realizing differentiated urban ecological governance. However, the existing zoning methods are overly focused on ecological functional attributes and fail to adequately consider the impacts of human activities, resulting in an insufficiently rational allocation of resources. Taking Guizhou Province as an example, using multi-source data and spatial analysis tools, this study proposed an ecological management zoning framework based on the coupling analysis of the blue-green infrastructure (BGI) network and gray infrastructure (GI) network. The results indicated that (1) the BGI network in the study area included 179 sources, with a total area of 54,228.80 km2, and 232 corridors. (2) There were 53 sources in the GI network, totaling 709.19 km2, and the corridors of the first, second, and third levels were 11,469.31 km, 6703.54 km, and 5341.30 km, respectively. (3) There were 606 barrier points identified, mainly distributed in the central part of the study area, and the total area of the disturbance zone was 1132.50 km2, which had the largest distribution in Qiandongnan, followed by Qiannan. (4) At the county scale, five ecological management zones were identified in the study area based on four indicators, namely, the source area ratio of BGI network, corridor density of BGI network disturbance zone area ratio, and density of barrier point. Then, we proposed targeted optimizations and restorations for each zone. This study organically linked ecological functional attributes and anthropogenic impacts to identify ecological management zones, which will provide new perspectives on synergies between ecological protection and economic development.